2015
DOI: 10.3389/fphar.2015.00296
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Pharmacological Organoprotection during Extracorporeal Circulation Targeting Ischemia-Reperfusion Injury

Abstract: Surgical correction of congenital cardiac malformations or aortocoronary bypass surgery in many cases implies the use of cardiopulmonary-bypass (CPB). However, a possible negative impact of CPB on internal organs such as brain, kidney, lung and liver cannot be neglected. In general, CPB initiates a systemic inflammatory response (SIRS) which is presumably caused by contact of blood components with the surface of CPB tubing. Moreover, during CPB the heart typically undergoes a period of cold ischemia, and the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 128 publications
1
18
0
Order By: Relevance
“…Several previous reports suggested that the hippocampus is sensitive to ischemia and reperfusion injury caused by CPB ( 1 , 29 ). In the present study, clear pathological damage and an increase in cell apoptosis and Caspase 3 expression levels in the hippocampus were observed in the CPB-injured rats, which confirmed that pathological changes occur in the hippocampus following CPB surgery.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Several previous reports suggested that the hippocampus is sensitive to ischemia and reperfusion injury caused by CPB ( 1 , 29 ). In the present study, clear pathological damage and an increase in cell apoptosis and Caspase 3 expression levels in the hippocampus were observed in the CPB-injured rats, which confirmed that pathological changes occur in the hippocampus following CPB surgery.…”
Section: Discussionmentioning
confidence: 95%
“…Cardiopulmonary bypass (CPB) is considered indispensable during heart operations, but the potential adverse effects on sensitive organs, such as the brain or the kidneys, cannot be ignored ( 1 ). In particular, many of the patients who undergo CPB surgery suffer from adverse cerebral outcomes, which may include stroke, postoperative cognitive dysfunction and transient ischemic attacks ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study demonstrated that SOCS‐3‐deficient macrophages had higher levels of M1 markers like IL‐1 β , IL‐6 and iNOS . Moreover, it is also identified that the over‐expression of SOCS‐3 induces M1 macrophages activation of co‐cultured macrophages, indicating its role in mediating polarization of macrophages through JAK/STAT signalling pathways . In addition, NF‐ κ B signalling pathway is considered to play a crucial role in M1 macrophage polarization.…”
Section: Regulatory Mechanisms Of Macrophage Polarization In Liver DImentioning
confidence: 99%
“…Although using liposomal clodronate to suppress macrophages is widely used in the current experiment and has capacity to reduce liver inflammation, it is less specific . Furthermore, it has been reported that KC‐specific inhibition of NF‐ κ B using decoy oligonucleotides displayed a therapeutic effect at the early stage of ALF, even applied to experimental animal models with more severe injury like liver ischaemia–reperfusion model.…”
Section: Macrophage‐targeted Therapy For Liver Diseasesmentioning
confidence: 99%
“…[1][2][3] Numerous treatment strategies have been proposed to reduce I/R injury, such as ischemic pre-conditioning, postconditioning, controlled reperfusion, and injection/infusion with various therapeutic agents. [4][5][6] The ultimate therapeutic objective of these treatments is to reduce oxidative stress, inflammation, vascular injury, while simultaneously providing an energy supply to the reperfused organ. Among several cellular events postulated to contribute to reperfusion injury, bursts of ROS occurring during early reperfusion have been shown to contribute to the evolution of a leukocyte-mediated inflammatory reaction that exacerbates reperfusion-induced tissue injury.…”
mentioning
confidence: 99%